Geometrización of the logical proposition and the learning in the match logical first year students of education faculty of the UNHEVAL Huánuco 2014 - Pozo Ortega, Fermin (2017)
The purpose of this study was to assess whether Geometrisation of propositional logic influencesthe Learning of Mathematical Logic in the first year students of the Faculty of Education Sciences ofthe National University Hermilio Valdizán, Huanuco 2014. They developed a applied research typeof quasi-experimental design, we worked with a control group and an experimental group, in whichthe geometrization of propositional logic developed during the first half of April to July 2014. Theresults of the posttest about learning logical connectives in both the experimental group and thecontrol group (Tables No 09 and 05) shows that there are differences; since in the experimentalgroup most students are placed in the remarkable level with notes ranging from 14-17, represented69% in dimension logical propositions, 75.9% in the logical connective dimension and 79, 3% in thedimension truth value of propositions while in the control group the majority of students are locatedat the level approved apprenticeship with notes ranging from 11-13 represented 57.1% in dimension logical propositions 60.7% in the logical connective dimension and 53.6% in the dimension truthvalue of propositions, demonstrating the significant influence of the geometrization of propositionallogic influences learning of mathematical logic. In conclusion, the calculated value of t = 11 islocated to the right of the critical value of t = 1.67 which is the rejection region, thus ruling out thenull hypothesis and accept the alternative hypothesis, ie the geometrization of propositional logicsignificantly influences the learning of mathematical logic in the first-year students of the Faculty ofEducational Sciences - 2014 National University.